2012
DOI: 10.1128/iai.06276-11
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum and Tannerella forsythia Induce Synergistic Alveolar Bone Loss in a Mouse Periodontitis Model

Abstract: ABSTRACTTannerella forsythiais strongly associated with chronic periodontitis, an inflammatory disease of the tooth-supporting tissues, leading to tooth loss.Fusobacterium nucleatum, an opportunistic pathogen, is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 50 publications
2
73
0
1
Order By: Relevance
“…1a). Several other bacteria have also been implicated, including but not limited to Tannerella forsythia, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum [31,32]. Given the diversity and numbers of other bacteria in and around the periodontal neighbourhood, then it is difficult to say with absolute certainty that particular periodontal pathogens are the sole cause of periodontitis.…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…1a). Several other bacteria have also been implicated, including but not limited to Tannerella forsythia, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum [31,32]. Given the diversity and numbers of other bacteria in and around the periodontal neighbourhood, then it is difficult to say with absolute certainty that particular periodontal pathogens are the sole cause of periodontitis.…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…The resulting infected area was swabbed for PCR analysis, and maxillae and mandibles were retrieved for alveolar bone resorption analysis [90]. T. forsythia and F. nucleatum caused more severe alveolar bone loss than other combinations of microbes tested, which the investigators had predicted due to their synergistic ability to form larger biofilms in vitro [91].…”
Section: Oral Infectionmentioning
confidence: 99%
“…The resulting infected area was swabbed for PCR analysis, and maxillae and mandibles were retrieved for alveolar bone resorption analysis [90]. T. forsythia and F. nucleatum caused more severe alveolar bone loss than other combinations of microbes tested, which the investigators had predicted due to their synergistic ability to form larger biofilms in vitro [91].A rat pup model was used to demonstrate a synergistic interaction between Streptococcus mutans and C. albicans during oral infection [92]. Pups were first screened and cleared of any endogenous S. mutans and C. albicans colonization, then infected with S. mutans for 23 days, followed by C. albicans for an additional 2 weeks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…forsythia, a common pathogen present in dental biofilms, is implicated in periodontitis. Its role in the disease process has been confirmed in animal models (1), and it has been demonstrated that the bacterium's ability to induce disease is enhanced when coinfected with other bacteria such as Fusobacterium nucleatum (22). Strikingly, T. forsythia depends on exogenous MurNAc, an essential peptidoglycan amino sugar, for growth.…”
Section: Discussionmentioning
confidence: 83%